Hubungan Stimulasi Ibu dengan Perkembangan Anak Pra Sekolah Usia 3-5 Tahun di KB RA Umi Sundari Kraksaan Kabupaten Probolinggo. - Nawwal Basid; Iis Hanifah; Homsiatur Rohmatin (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Development is the increasing ability of the body to structure and function more complexly, in an orderly and predictable pattern. One of the aspects that assist the adequacy of child development is parents' support. One of the factors that influence the development of toddlers is stimulation. Stimulation is trigger that comes from the child's external environment. The purpose of this study was to determine whether there is a relationship between maternal stimulation and the development of pre-school children aged 3-5 years. This research is a correlational analytic study with a cross sectional approach. They were taken using a complete sampling approach on a population of 30 persons and a sample of 30 people. The research instrument used was a questionnaire. The frequency distribution is used for univariate data analysis, and the Fisher’s Exact Test alternative is used for bivariate data analysis. The result showed that 22 mothers provided good stimulation and 8 mothers gave less stimulation. From the results of the KPSP, it showed that there were 20 children with appropriate development, 4 children with doubts, and 6 children with deviations. Based on the Fisher’s Exact Test alternative, it was known that the P value is 0.000 with α 0.05. Because the significance value is <α, then H0 is rejected and H1 is accepted, indicating that there is a correlation between stimulation and the development of pre-school children aged 3-5 years in KB RA Umi Sundari Kraksaan, Probolinggo Regency. It is hoped that the results of this study would help parents who have children give adequate stimulation for their children's growth.